Various biofilm matrices of the emerging pathogen Staphylococcus lugdunensis: exopolysaccharides, proteins, eDNA and their correlation with biofilm mass. Issue 1 (2nd January 2020) - Ravaioli, Stefano; Campoccia, Davide; Speziale, Pietro; Pietrocola, Giampiero; Zatorska, Beata; Maso, Alessandra; Presterl, Elisabeth; Montanaro, Lucio; Arciola, Carla Renata
Abstract: Staphylococcus lugdunensis is an emerging high-virulent pathogen causative of hospital-acquired infections. Biofilm formation is a complex pathogenic process that leads to well-established bacterial communities. There is a paucity of data on the composition of the biofilm matrix among S. lugdunensis strains. Here, twenty-two S. lugdunensis clinical isolates, mainly from orthopaedic infections but also from other clinical sources, were sub-grouped by ribotyping and dendrogram analysis. Biofilms were analysed by fluorimetric methods based on FITC-Wheat Germ Agglutinin, SYPRO Ruby and TOTO-1 dyes to detect exopolysaccharides, proteins and extracellular DNA (eDNA), respectively. Biofilm morphology was investigated under confocal laser scanning microscopy (CLSM). Isolates displayed intriguing diversities in biofilm mass and matrix composition. The content of exopolysaccharides was found to be to be strongly associated with the biofilm mass (R 2 = 0.882), while the content of proteins turned out to be weakly (R 2 = 0.465) and that of eDNA very weakly associated (R 2 = 0.202) to the biofilm mass.